Механізм подолання надмірної соціальноекономічної диференціації регіонів - Родченко, В.Б. (Стратегія і механізми регулювання промислового розвитку, 2013)
Досліджено показники оцінки соціально-економічної диференціації регіонів. Уточнено розуміння категорії «диференціація». Запропоновано при формуванні механізму подолання надмірної соціально-економічної диференціації регіонів розглядати три ключові складові, а саме економічну, перерозподілу та соціальну. Визначено відмінності природи кожної зі складових. Запропоновано підхід до розробки пріоритетів механізму регулювання надмірної соціально-демографічної диференціації, заснований на системі індексів. Исследованы показатели оценки социально-экономической дифференциации регионов. Уточнено понимание категории «дифференциация». Предложено при формировании механизма преодоления чрезмерной социально-экономической дифференциации регионов рассматривать три ключевые составляющие, а именно экономическую, перераспределения и социальную. Определены различия природы каждой из составляющих. Предложен подход к разработке приоритетов механизма регулирования чрезмерной социально-демографической дифференциации, основанный на системе индексов. This article investigates evaluation indicators of socioeconomic differentiation of regions. The meaning of the differentiation category is clarified. The formation of the mechanism to overcome excessive socioeconomic differentiation of regions has three key components, namely, economic, social and redistribution components. The difference between each other components’ nature is determined. The author defines an economic component as the territorial unevenness that is caused by the concentration of production processes in the centers of economic activity, redistribution component - the need to ensure the unity of the processes of social and economic security all over the country and the alignment of economic development, social - by providing a uniform level of social security of residents in all regions, independently from the state of the economic development. The system of indices of socioeconomic development is built and the evaluation indicators of regional differentiation in 2012 are calculated. To develop a priority mechanism for regulating excessive socio-demographic differentiation, the average values are calculated for the groups of indices. It’s determined that there is a big disproportional level between social and demographic development of the regions. It is concluded that in the areas with a high demographic development the development of industrial and social infrastructure and capacity to implement such capabilitieswill be the first priority. In the areas where the level of social development is higher as compared to the population growth the social infrastructure and ensurance of high standards of demographic development are the key objectives. This approach will limit the “consumer” needs of the regions-outsiders and promote sustainable development and the gradual equalization of disparities in the regional development.